The 16-week sonographic findings in fetuses with increased nuchal translucency and a normal array. (12th December 2022) - Zhen, Li; Pan, Min; Li, Yan-Ting; Cao, Qun; Xu, Li-Li; Li, Dong-Zhi
Abstract: Objective: The aim of this prospective study is to evaluate the performance of the intermediate 16-week ultrasound in fetuses with increased nuchal translucency (NT) and a normal chromosomal microarray analysis (CMA). Methods: During a one-year period, a detailed ultrasound was performed at 16 week' gestation for patients with an increased NT (≥3.5 mm) and normal CMA. Pregnancy work-up included a traditional 22-week ultrasound scan, an echocardiography, and the option of a 10-gene Rasopathy panel after a normal 16-week scan. Abnormal findings and pregnancy outcomes were collected and analyzed. Results: In 52 fetuses with an isolated increased NT and normal CMA, 14 (26.5%) were noted to have structural defects on the 16-week ultrasound. Intrauterine fetal death occurred in one (1.9%) case identified by the 16-week scan. Of the remaining 37 cases, six opted for a RASopathy panel. In this group, one case of Noonan syndrome was detected. One case of unilateral duplex kidney had not been found until the 22-week scan. One case of fetal growth restriction was identified in the third trimester. The remaining 34 cases proceeded with normal ultrasound to term. Conclusion: The 16-week ultrasound scan performed on fetuses with increased NT and normal CMA could detect the majority of structural abnormalities that are expected to be identified traditionally at 20–24 weeks.